Predictors of muscle strength in older individuals - Raso,Vagner (2016)
PURPOSE: To analyze possible relationships between load, body mass and lean body mass in an effort to provide norm-referenced standards for the one repetition maximum test and to predict whole body muscle strength (WBMS) in older individuals. METHODS: We measured body mass, lean body mass and the one repetition maximum (1RM) test in different exercises in 189 older men and women aged 61 to 82 years. Whole body muscle strength (WBMS) was calculated as the sum of loads of the different exercises. RESULTS: For women, the inclusion of body mass or lean body mass increased the R2 from 0.41 to 0.82, and yielded the following equation: WBMS = 75.788 + (2.288 × load in kg of latissimus pull down) + (0.799 × lean body mass in kg). For men, the inclusion of either body mass (WBMS = 290.33 - [3.140 × age in years] + [1.236 × body mass in kg] + [1.549 × load in kg of leg press]) or, in particular, lean body mass (WBMS = 343.25 - [3.298 × age in years] + [.415 × lean body mass in kg] + [1.737 × load in kg of leg press]) decreased the standard error of the estimate. CONCLUSION: Our data support the idea that load correlates with body mass and lean body mass and that the load used for a specific exercise is significantly associated with WBMS, thereby permitting the development of a predictive model of WBMS with increased accuracy.